2019
DOI: 10.1111/imm.13098
|View full text |Cite
|
Sign up to set email alerts
|

Functionally significant metabolic differences between B and T lymphocyte lineages

Abstract: Summary Activation of B and T lymphocytes leads to major remodelling of the metabolic landscape of the cells enabling their post‐activation functions. However, naive B and T lymphocytes also show metabolic differences, and the genesis, nature and functional significance of these differences are not yet well understood. Here we show that resting B‐cells appeared to have lower energy demands than resting T‐cells as they consumed lower levels of glucose and fatty acids and produced less ATP. Resting B‐cells are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 75 publications
5
29
1
Order By: Relevance
“…IRE1 via XBP1s controls eosinophil, DC, and plasma cell development (Reimold et al, 2001;Iwakoshi et al, 2007;, which contribute to neuroinflammation in MS and Experimental Autoimmune Encephalomyelitis (EAE), the mouse model of MS (Greter et al, 2005;Wensky et al, 2005;Mundt et al, 2019;Pröbstel et al, 2020). Furthermore, DCs and plasma cells show constitutive UPR activation and display an elevated protein synthesis rate in steady state (Osorio et al, 2014;Khalsa et al, 2019;Mendes et al, 2020). In these cell types, XBP1s maintains ER architecture, whereas RIDD controls functional aspects, including antigen cross-presentation and cDC1s survival, or immunoglobulin production by plasma cells (Benhamron et al, 2014;Osorio et al, 2014;Tavernier et al, 2017).…”
Section: The Upr In Immune Cell Function In Physiological and Inflammatory Statesmentioning
confidence: 99%
“…IRE1 via XBP1s controls eosinophil, DC, and plasma cell development (Reimold et al, 2001;Iwakoshi et al, 2007;, which contribute to neuroinflammation in MS and Experimental Autoimmune Encephalomyelitis (EAE), the mouse model of MS (Greter et al, 2005;Wensky et al, 2005;Mundt et al, 2019;Pröbstel et al, 2020). Furthermore, DCs and plasma cells show constitutive UPR activation and display an elevated protein synthesis rate in steady state (Osorio et al, 2014;Khalsa et al, 2019;Mendes et al, 2020). In these cell types, XBP1s maintains ER architecture, whereas RIDD controls functional aspects, including antigen cross-presentation and cDC1s survival, or immunoglobulin production by plasma cells (Benhamron et al, 2014;Osorio et al, 2014;Tavernier et al, 2017).…”
Section: The Upr In Immune Cell Function In Physiological and Inflammatory Statesmentioning
confidence: 99%
“…However, data on B cell lymphocyte metabolism is relatively scarce, as the previously mentioned studies primarily concentrated on T lymphocytes. Recent evidence showed that resting B cells seem to have lower energy requirements than resting T cells as they consumed less glucose and fatty acids and, consequently, produced less ATP [ 63 ]. Nevertheless, resting B cells primarily rely on OXPHOS to meet their metabolic demands and have a higher mitochondrial mass [ 63 ].…”
Section: Distinct Energetic Profiles Of Immune Cellsmentioning
confidence: 99%
“…Recent evidence showed that resting B cells seem to have lower energy requirements than resting T cells as they consumed less glucose and fatty acids and, consequently, produced less ATP [ 63 ]. Nevertheless, resting B cells primarily rely on OXPHOS to meet their metabolic demands and have a higher mitochondrial mass [ 63 ]. Despite these differences in the resting state, B cells share some metabolic characteristics with T cells upon activation.…”
Section: Distinct Energetic Profiles Of Immune Cellsmentioning
confidence: 99%
“…Increased plasma glucose usage may restrict this nutrient from Tfh cells; however, Tfh cells downregulate glycolysis in response to expression of their lineage defining transcription factor B cell lymphoma 6 ( Bcl6 ). The change in metabolic preference is concurrent with a change in activation state and is functionally specific to immune cell types ( Khalsa et al, 2019 ). Feedback mechanisms through cytokine signaling, such as anti-inflammatory interleukin-10 ( IL -10), eventually contribute to reduced activation states to prevent continuous activation and cellular exhaustion ( Couper et al, 2008 ; Saraiva and O’Garra, 2010 ; Khalsa et al, 2019 ).…”
Section: Immunometabolismmentioning
confidence: 99%